The opportunity costs of birth in Australia: Hospital resource savings for a post–COVID‐19 era - Callander, Emily J. (Birth, 2021)
BACKGROUND: COVID‐19 caused significant disruptions to health systems globally; however, restricting the family presence during birth saw an increase in women considering community birth options. This study aimed to quantify the hospital resource savings that could occur if all low‐risk women in Australia gave birth at home or in birth centers. METHODS: A whole‐of‐population linked administrative data set containing all women (n = 44 498) who gave birth in Queensland, Australia, between 01/07/2012 and 30/06/2015 was reweighted to represent all Australian women giving birth in 2017. A static microsimulation model of woman and infant health service resource use was created based on 2017 data. The model was comprised of a base model, representing "current" care, and a counterfactual model, representing hypothetical scenarios where all low‐risk Australian women gave birth at home or in birth centers. RESULTS: If all low‐risk women gave birth at home in 2017, cesarean rates would have reduced from 13.4% to 2.7%. Similarly, there would have been 860 fewer inpatient bed days and 10.1 fewer hours of women's intensive care unit time per 1000 births. If all women gave birth in birth centers, cesarean rates would have reduced to 6.7%. In addition, over 760 inpatient bed days would have been saved along with 5.6 hours of women's intensive care unit time per 1000 births. CONCLUSIONS: Significant health resource savings could occur by shifting low‐risk births from hospitals to home birth and birth center services. Greater examination of Australian women's preferences for home birth and birth center birth models of care is needed.